Monetary Integration in West Africa – Development and Functioning of CFA Frank Area - Zaremba, Michał (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article aims to present the development and history of the African CFA franc zone, which is the official currency in two groupings of African integration – the West African Economic and Monetary Union and Economic and Monetary Community of Central Africa. In the first part of the paper focuses on the theoretical aspects of monetary integration, while the second has been devoted to the analysis of monetary integration processes on the continent.